Pengembangan PSBBOT: Bot Telegram Berbasis Python untuk Pengelolaan Foto dan Data Pasang Baru - I Made Arya Budhi Saputra; Ni Made Dewi Kansa Putri; Made Krisnawan (Universitas Respati Indonesia, 2026)
In the New Installation (PSB) operations at PT Bali Insan Perkasa, data and documentation management are conducted manually using the Telegram application, creating efficiency challenges, particularly in searching and verifying evidence data and digital BA. The large volume of data results in significant processing time and increases the risk of errors. Therefore, this study proposes the development of a Python-based Telegram Bot integrated with Microsoft Excel to automate the management of photos and PSB data. The bot is designed to automatically receive, categorize, and store data in accordance with the predetermined installation order, enabling efficient integration with existing infrastructure. The research methods include system analysis, bot design, and evaluation through functional testing of the bot in accurately managing data and ensuring its ease of use by technicians and admins. The implementation results demonstrate improved operational efficiency, accelerated documentation processes, and reduced error risks, positively impacting company productivity and technician satisfaction. This study provides strategic insights for implementing similar automation technologies in other industries facing data management challenges.